Living culture and resilience through tourism: The Mushily Cultural Center and Other Tsáchila Initiatives - Porsani, Juliana; Lehtilä, Kari; Calazacón, Budy (Whispers from below: Community-based tourism and (other) Ecuadorian initiatives for alternative economies: A closer look, 2026)
Tourism among the Tsáchila people is a form of resistance and a means of preserving their identity. Through projects such as the Mushily Cultural Center, shamanism and the role of women are being revitalized as cornerstones of collective memory. This community-led self-management enables them to confront economic marginalization, transforming their ancestral heritage into a political tool that ensures the defense of their territory and the continuity of their traditions in the face of globalization.